Blombos Cave: Middle Stone Age ochre differentiation through FTIR, ICP OES, ED XRF and XRD. (6th June 2016) - Moyo, Stanley; Mphuthi, Dikeledi; Cukrowska, Ewa; Henshilwood, Christopher S.; van Niekerk, Karen; Chimuka, Luke
Abstract: In Africa, ochre is ubiquitous in archaeological sites after 100 ka and likely served a symbolic role in the lives of prehistoric people. Archaeological excavation of the c. 100–72 ka Middle Stone Age (MSA) levels at Blombos Cave (BBC) located in the southern Cape, South Africa, have yielded significant amounts of ochre as artefacts or residues. Although recent archaeological evidence from BBC and elsewhere has provided remarkable insights into the ways that ochre was used, for example its use as a pigmented 'paint', the significance of ochre can be further understood by studying its procurement pattern. To this end, the geochemical characterisation of recovered ochre can tell us about the temporal and spatial variation present at a site. The analysis of BBC ochre was accomplished using FTIR, ED XRF, ICP OES and XRD with the aim of determining the mineral and elemental composition variability of ochre across layers and thereby gauging whether there were preferred or different ochre procurement patterns or sources over time. For example, it was found that ochre residues from the c. 100 ka CP layer had kaolinite and quartz as the principal minerals, while ochre residues from the c. 97 ka CJ layer consisted mainly of calcite and quartz. Thus, mineral composition can indicate procurement of different sources of ochre during the various stages of the cave occupation. Elemental analysis of ochre residues from the c. 77–72 ka Still Bay, CJ and CP layers also revealed differences in minor and trace elements. These findings seem to indicate some differences in the ochre from these levels and can also be taken as an indication of different ochre sourcing.